Functional Magnetic Resonance Imaging Correlates of Ventral Striatal Deep Brain Stimulation for Poststroke Pain. Issue 2 (3rd August 2020) - Jones, Stephen E.; Lempka, Scott F.; Gopalakrishnan, Raghavan; Baker, Kenneth B.; Beall, Erik B.; Bhattacharyya, Pallab; Huang, Xuemei; Lin, Jian; Chen, Jacqueline; Lowe, Mark J.; Malone, Donald A.; Machado, Andre G.
Abstract: Objective: Deep brain stimulation (DBS) for pain has largely been implemented in an uncontrolled manner to target the somatosensory component of pain, with research leading to mixed results. We have previously shown that patients with poststroke pain syndrome who were treated with DBS targeting the ventral striatum/anterior limb of the internal capsule (VS/ALIC) demonstrated a significant improvement in measures related to the affective sphere of pain. In this study, we sought to determine how DBS targeting the VS/ALIC modifies brain activation in response to pain. Materials and Methods: Five patients with poststroke pain syndrome who were blinded to DBS status (ON/OFF) and six age‐ and sex‐matched healthy controls underwent functional magnetic resonance imaging (fMRI) measuring blood oxygen level‐dependent activation in a block design. In this design, each participant received heat stimuli to the affected or unaffected wrist area. Statistical comparisons were performed using fMRI z‐maps. Results: In response to pain, patients in the DBS OFF state showed significant activation ( p < 0.001) in the same regions as healthy controls (thalamus, insula, and operculum) and in additional regions (orbitofrontal and superior convexity cortical areas). DBS significantly reduced activation of these additional regions and introduced foci of significant inhibitory activation ( p < 0.001) in the hippocampi when painful stimulation was applied to the affected side. Conclusions: These findings suggest that DBS of the VS/ALIC modulates affective neural networks.